Anthosactis janmayeni Danielssen, 1890, a rare high-arctic sea anemone - Riemann-Zürneck, K. (Polar Biology, 1997)
Three specimens of the high-arctic sea anemone Anthosactis janmayeni Danielssen, 1890, collected during the Swedish YMER expedition in 1980 and ARK VII/2 of the German RV ‘‘Polarstern’’ in 1990, allow a redescription of this rarely reported species. Data provided by Russian scientists suggest that A. janmayeni is confined to localities where the high arctic conditions prevail throughout the year.